2012
DOI: 10.3126/kumj.v8i4.6241
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Simian Crease in Normal Nepalese Children

Abstract: Backgroud Simian crease is usually associated with some chromosomal anomalies and syndromes but it is also seen in some populations without any chromosomal defects. Objective To see the incidence of simian crease in children without chromosomal anomalies and to detect the Ethnic group variations. Methods A prospective study in children attending the paediatric outpatient department of Manipal Teaching Hospital, Pokhara. –2,067 children were screened randomly from the 1st June 2007 to the 31st December 2007. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…This was in line with a study conducted in India [ 8 ] and a study conducted among Korean and Iran populations also revealed significantly higher in males [ 7 , 16 ]. A similar report was found among different studies [ 2 , 11 , 24 ]. In the present study, males had higher odds of sydney crease pattern than normal crease pattern.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This was in line with a study conducted in India [ 8 ] and a study conducted among Korean and Iran populations also revealed significantly higher in males [ 7 , 16 ]. A similar report was found among different studies [ 2 , 11 , 24 ]. In the present study, males had higher odds of sydney crease pattern than normal crease pattern.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the prevalence of the simian crease pattern was 5% (95% CI: 4.1, 5.9). It was comparatively similar to studies conducted in Nigerian (4.1%) and Jewish (4.6%) [ 2 , 8 ], but lower than other studies conducted in a different part of the world [ 7 , 8 , 11 , 13 , 14 , 24 ]. On the other side, the finding of this study was higher than studies conducted in Japanese (4%), Swiss (1.2%), and Germans (2.8%) [ 2 , 8 , 9 ] ( Fig.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…). Among these variations, the simian crease stands out as the most medically researched owing to its abnormal appearance (Malla et al, ). Although nearly 10% of the population with a normal karyotype have a simian crease unilaterally and around 5% bilaterally, this crease is most often a phenotypic indicator of various chromosomal disorders and syndromes (Sunilkumar, ) (Figs.…”
Section: Introductionmentioning
confidence: 99%